The importance of a birth plan for the parturient’s autonomy (Research, Society and Development, 2022)
Objective: To highlight the importance of a birth plan, its benefits, and incentives, as well as that it should be created by a nurse and how pregnant women understand and use a BP. Methodology: This is an integrative review study with a qualitative approach. Results: The number of pregnant women who know about and use a birth plan is small due to a lack of guidance from professionals unaware of such a document. The importance of application of this document presents the parturient with great satisfaction and gives autonomy and voice to these women. Conclusion: According to this study, it can be said that a Birth Plan is a technology that enhances humanized care for women and newborns and has contributed to improving the quality of obstetric care.